6x+5-1/2=2x+3

Simple and best practice solution for 6x+5-1/2=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5-1/2=2x+3 equation:



6x+5-1/2=2x+3
We move all terms to the left:
6x+5-1/2-(2x+3)=0
We get rid of parentheses
6x-2x-3+5-1/2=0
We multiply all the terms by the denominator
6x*2-2x*2-1-3*2+5*2=0
We add all the numbers together, and all the variables
6x*2-2x*2+3=0
Wy multiply elements
12x-4x+3=0
We add all the numbers together, and all the variables
8x+3=0
We move all terms containing x to the left, all other terms to the right
8x=-3
x=-3/8
x=-3/8

See similar equations:

| 61x+2+42=86x-2 | | -3-3x=14(2x+7) | | -2(3x+4)+7=-10 | | 9x-48=6 | | y=5^2+4 | | –19k=–18−20k | | -18=6y7y | | 2n-22=2(1-2n) | | 118=-8+9n | | 0.6x0.7= | | 7-3x=5x+10 | | -9c+70=70 | | 24-t=5t | | z+5=5z-3 | | 11=3-(1/4)x | | 2x+4(2)=16 | | -8y+2(y+4)=-10 | | 6j=6 | | 196-4.7x=215-6.7x | | 2π/x=3/2 | | 10-3(2x-4)=-44 | | 4(2d-5)=20 | | 9+7p=9p-3 | | -3n+9=9-3n | | 5x−6=3x+18 | | 0.39x=1 | | 21x+132=86x+2 | | x-47=-10 | | 2π/x=1.5 | | -56=8n | | -10+2-8q=10-5q | | p+10=12 |

Equations solver categories